2003
DOI: 10.1074/jbc.m211888200
|View full text |Cite
|
Sign up to set email alerts
|

AF-6 Controls Integrin-mediated Cell Adhesion by Regulating Rap1 Activation through the Specific Recruitment of Rap1GTP and SPA-1

Abstract: In the present study, we showed that SPA-1, a Rap1 GTPase-activating protein (GAP), was bound to a cytoskeleton-anchoring protein AF-6. SPA-1 and AF-6 were co-immunoprecipitated in the 293T cells transfected with both cDNAs as well as in normal thymocytes. In vitro binding studies using truncated fragments and their mutants suggested that SPA-1 was bound to the PDZ domain of AF-6 via probable internal PDZ ligand motif within the GAP-related domain. The motif was conserved among Rap1 GAPs, and it was shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 28 publications
(26 reference statements)
4
77
0
Order By: Relevance
“…This difference may be due to variations in the Afadin isoforms expressed, their ability to bind to actin, or the potential absence of an effect of Afadin on ␤1 integrin in MCF10A cells. Additionally, the PDZ binding motif of Afadin has been reported to bind to Rap1GAP, which inactivates Rap1 (Su et al, 2003). It is possible that JAM-A and Rap1GAP compete for binding of Afadin, because they interact with the same protein domain, and such competitive binding could produce cell-type-specific responses.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to variations in the Afadin isoforms expressed, their ability to bind to actin, or the potential absence of an effect of Afadin on ␤1 integrin in MCF10A cells. Additionally, the PDZ binding motif of Afadin has been reported to bind to Rap1GAP, which inactivates Rap1 (Su et al, 2003). It is possible that JAM-A and Rap1GAP compete for binding of Afadin, because they interact with the same protein domain, and such competitive binding could produce cell-type-specific responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism is unclear. It is conceivable that RapGAPs such as Rap1GAP and SPA-1, which were previously reported to interact with afadin, 37 could be involved. Indeed, we recently reported that the interaction of Rap1 with afadin increases the activity of Rap1 in NIH3T3 cells and that this interaction prevents the SPA-1-induced inactivation of Rap1.…”
Section: Discussionmentioning
confidence: 99%
“…The similar effects of Rap1GAP overexpression and downregulation may indicate that Rap1GAP functions as part of a macromolecular complex, where alterations in Rap1GAP expression impact stoichiometry. Besides interacting with Rap, Rap1GAP binds to heterotrimeric G protein ␣ subunits (27,33,35) and AF6 (43,55), a protein that associates with activated Rap and localizes to cell/cell junctions (7).…”
Section: Discussionmentioning
confidence: 99%